2014
DOI: 10.1177/1932296814536289
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Whole Body Vibration on Skin Blood Flow and Nitric Oxide Production

Abstract: Neurological and Microvascular FunctionNeuropathies are among the most common complications of diabetes mellitus 1 and are the cause of more than 60% of all nontraumatic amputations in the United States.2 Neuropathy is a set of syndromes, each with a wide range of clinical and subclinical manifestations, the most common of which is distal symmetric polyneuropathy (DSPN).1,3 Distal symmetric polyneuropathy occurs in both type I and type II diabetes, and the symptoms range considerably. Some patients experience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 29 publications
2
57
0
Order By: Relevance
“…However, using high frequency, Button et al (13) and Hazell et al (14) reported no significant difference in local blood flow in healthy participants between vibration and control groups. In diabetic patients, and in contrast to Lythgo et al (12) findings on healthy subjects, Johnson et al (15) showed low frequency (26 Hz) and low amplitude (2 mm) vibration increased blood flow (to the skin area in the feet). Similarly, Sañudo et al (16) revealed significant improvement of femoral artery blood flow after 12 weeks of WBV training in diabetic patients (12)(13)(14)(15)(16) Hz, 4 mm, 3 days a week).…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…However, using high frequency, Button et al (13) and Hazell et al (14) reported no significant difference in local blood flow in healthy participants between vibration and control groups. In diabetic patients, and in contrast to Lythgo et al (12) findings on healthy subjects, Johnson et al (15) showed low frequency (26 Hz) and low amplitude (2 mm) vibration increased blood flow (to the skin area in the feet). Similarly, Sañudo et al (16) revealed significant improvement of femoral artery blood flow after 12 weeks of WBV training in diabetic patients (12)(13)(14)(15)(16) Hz, 4 mm, 3 days a week).…”
Section: Introductionmentioning
confidence: 71%
“…Baum et al (2) revealed FBS and HbA1c levels in type II diabetics were reduced by approximately 6.3% and 0.3% respectively after 12 weeks of WBV using a horizontal swinging platform (30-35 Hz, 2 mm amplitude, 8 bouts of 30 seconds, 3 days a week). More recently, del Pozo-Cruz et al (9) reported 12 weeks of WBV training (12)(13)(14)(15)(16) Hz, 4 mm, 3 days a week) significantly improved levels of FBS and HbA1c. However, in contrast to the beneficial effects reported by Baum et al (2) and del Pozo-Cruz et al (9), Behboudi et al (8) found that FBS and HbA1c levels were not significantly improved after 8 weeks of WBV training (30 Hz, 2 mm, 3 days a week).…”
Section: Introductionmentioning
confidence: 97%
“…Johnson et al (2014) with a single session, also observed a significant increase in the skin blood flow. These findings are of clinical importance due to endothelial dysfunction with capillary alterations and impairment of the blood flow in this population group (Rajendran et al, 2013;Coelho et al, 2011;Widmer and Lerman 2014;Murray et al, 2004).…”
Section: Effects On Clinical Populationsmentioning
confidence: 83%
“…In patients with diabetes, increments in the blood flow speed and maximum diastolic velocity after WBV were observed (Sañudo et al, 2013;Johnson et al, 2014). Johnson et al (2014) with a single session, also observed a significant increase in the skin blood flow.…”
Section: Effects On Clinical Populationsmentioning
confidence: 92%
See 1 more Smart Citation